1991
DOI: 10.1073/pnas.88.14.6323
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 7 receptor engagement stimulates tyrosine phosphorylation, inositol phospholipid turnover, proliferation, and selective differentiation to the CD4 lineage by human fetal thymocytes.

Abstract: The purposes of this study were to elucidate the effects of recombinant human interleukin 7 (rhIL-7) on proliferation as well as differentiation of human fetal thymocytes and to analyze the biochemical nature ofthe IL-7 receptorlinked transmembrane signal. In the absence of costimulants, rhIL-7 stimulated the in vitro proliferation and colony formation of CD4+CD8' double-positive immature fetal thymocytes. Furthermore, rhIL-7 promoted partial differentiation of immature thymocytes with a selective advantage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Although we chose IL-7 because of its ability to simultaneously stimulate thymopoiesis, 14,43 increase T-cell proliferation, 44,45 and prolong survival of mature T cells, 46 it was not clear before this study which if any of these functions of IL-7 would be effective in T-cell recovery in ICL. ICL T cells express high levels of activation and proliferation markers 3 and, as recently reported, are prematurely senescent.…”
Section: Discussionmentioning
confidence: 99%
“…Although we chose IL-7 because of its ability to simultaneously stimulate thymopoiesis, 14,43 increase T-cell proliferation, 44,45 and prolong survival of mature T cells, 46 it was not clear before this study which if any of these functions of IL-7 would be effective in T-cell recovery in ICL. ICL T cells express high levels of activation and proliferation markers 3 and, as recently reported, are prematurely senescent.…”
Section: Discussionmentioning
confidence: 99%
“…It would be of interest were the homologous part to play a role in the interaction of tyrosine kinases. Several cytokines, such as IL-2, IL-3, and IL-7, have been reported to induce tyrosinephosphorylation of cellular proteins and activation of tyrosine kinases (30)(31)(32). In contrast, the growth factor receptors such as epidermal growth factor receptor, colony-stimulating factor 1 receptor, and platelet-derived growth factor receptor, which possess the tyrosine kinase domain in the cytoplasmic region, do not contain box 1-and box 2-like seProc.…”
Section: Discussionmentioning
confidence: 99%
“…Some cytokines, such as IL-2, IL-3, and IL-7, phosphorylate tyrosine in cellular proteins, including the receptor (30)(31)(32). We examined whether gp130 was tyrosine-phosphorylated in response to IL-6.…”
mentioning
confidence: 99%
“…IL-7 was originally identified by its ability to induce proliferation of B cell progenitors in vitro and in vivo and was subsequently shown to stimulate T lymphopoiesis. [17][18][19][20][21][22][23][24][25][26] Recently, we have shown that administration of IL-7 significantly enhances immune recovery in mice after T celldepleted BMT. 27 Therefore, production of IL-7 may be one of the mechanisms regulating de novo production of T lymphocytes after BMT.…”
mentioning
confidence: 99%